A Tobacco Syringe Agroinfiltration-Based Method for a Phytohormone Transporter Activity Assay Using Endogenous Substrates - Zhao, Jiangzhe; Ju, Min; Qian, Jiayun; Zhang, Mengyuan; Liu, Ting; Zhang, Kewei (Frontiers in Plant Science, 2021)
Phytohormones are a group of small chemical molecules that play important roles in plant development, metabolism, and stress responses. Phytohormones often have distinct sites of biosynthesis and signaling perception, thereby requiring long or short-distance transportation. Compared to the biosynthesis and signal transduction, the transport of phytohormones across the cells and organs are poorly understood. Transporter activity assay is a bottleneck for the functional characterization of novel phytohormone transporters. Herein, we report a tobacco syringe agroinfiltration and liquid chromatography tandem mass spectrometry (LC-MS/MS) based method (TSAL) for phytohormone transporter activity assay using endogenous hormones in tobacco (Nicotiana benthamiana) leaves. The transporter activity assay using this method does not require isotope-labeled substrates and is convenient to be performed for multiple-substrate screening using the endogenous hormones in tobacco leaves. The transporter activities of three known hormone transporters including AtABCG25 for abscisic acid, AtABCG16 for jasmonate and AtPUP14 for cytokinin, were all successfully validated by this method. Cytokinins were characterized to be the preferring substrates of an unknown maize (Zea mays) transporter ZmABCG43 by this method. Transporter activities of ZmABCG43 towards cytokinins were further confirmed in a cytokinin long-distance transport mutant atabcg14 by gene complementation. Collectively, TSAL method has the potential to be used for the basic characterization of the substrates of novel phytohormone transporters, or for the screening of novel transporters for a specific phytohormone in large scale.